To study the properties of high strength concrete using ordinary portland cement (OPC) with silica fume (Microsilica) by replacement method in terms of compressive strength and absorption / Noor Azman Mastor - Mastor, Noor Azman (1996)
The use of high strength concrete (HSC) in structures is increasing worldwide and has begun to make an impact in Malaysia. In the past two semesters, the studies have been carried out on high strength concrete with the effect of silica fumes and the method of concrete mix used was by addition. The main purpose of study is to engage into high strength concrete with the effect of silica fume by replacement method. The influence on concrete under wet and hardened condition have also been observed. The study has investigated the effects on behavior of microsilica concrete with variation of silica fume (microsilica) quantity. A grade 60 concrete was designed at varying quantity of silica fume, replaced from the absolute weight of cement used in mix design. For the strength development and permeability , the tests were carried out on 150mm cubes at ages 28 days and 60 days after the mixing. Types of testing performed were Slump test, Compressive strength test and Initial Surface Absorption Test (ISAT). The tests have shown the optimum percentages of silica fume that gave the best performance of high strength concrete. The previous studies have proven that the effect of HSC with addition of silica fume has a significant improvement in performance in terms of durability and strength. From the current study it has been found that with the replacement of silica fume the improvement in performance is also significant as compared to the previous method. A thorough study on strength development and the permeability in terms of absorptivity of densified microsilica concrete has been carried out with specific objectives in finding out their workability, strength development, impermeability and durability. The significant results achieved show that for strength development and durability the optimum dosage by replacement of microsilica for cement content of 15% and 16% has given the best performance respectively.